2022
DOI: 10.3389/fsurg.2022.845125
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Erector Spinae Nerve Block for Pain Control After Spinal Surgeries: An Updated Systematic Review and Meta-Analysis

Abstract: BackgroundErector spinae plane block (ESPB), as a regional anesthesia modality, is gaining interest and has been used in abdominal, thoracic and breast surgeries. The evidence on the efficacy of this block in spinal surgeries is equivocal. Recently published reviews on this issue have concerning limitations in methodology.MethodsA systematic search was conducted using the PubMed, Scopus, Embase, and Cochrane Central Register of Controlled Trials (CENTRAL). Randomized controlled trials (RCTs) that were done in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…A closer examination of one of the most recent meta-analyses by Duan et al, based on no less than 13 individual studies, shows inconclusive evidence for a clear-cut benefit from ESPB, even when exclusively compared to no block or placebo. 49 A very recent adult RCT further supports this, finding no or only a minimal effect of using ESPB in this context. 50 If it is not possible to show a clear-cut beneficial effect of ESPB, in a situation where the anatomical reasoning might explain the efficacy, one cannot help but question whether the hypothesized nerve-blocking effect of FPBs is clinically relevant.…”
Section: General Considerationsmentioning
confidence: 74%
See 1 more Smart Citation
“…A closer examination of one of the most recent meta-analyses by Duan et al, based on no less than 13 individual studies, shows inconclusive evidence for a clear-cut benefit from ESPB, even when exclusively compared to no block or placebo. 49 A very recent adult RCT further supports this, finding no or only a minimal effect of using ESPB in this context. 50 If it is not possible to show a clear-cut beneficial effect of ESPB, in a situation where the anatomical reasoning might explain the efficacy, one cannot help but question whether the hypothesized nerve-blocking effect of FPBs is clinically relevant.…”
Section: General Considerationsmentioning
confidence: 74%
“…A literature search reveals several adult meta‐analyses (also including teenagers and adolescents) regarding the effect of ESPB in the context of spine surgery. A closer examination of one of the most recent meta‐analyses by Duan et al, based on no less than 13 individual studies, shows inconclusive evidence for a clear‐cut benefit from ESPB, even when exclusively compared to no block or placebo 49 . A very recent adult RCT further supports this, finding no or only a minimal effect of using ESPB in this context 50 .…”
Section: Pediatric Fascial Plane Blocksmentioning
confidence: 99%
“…On the one hand, a meta-analysis conducted by Xiao et al 44 demonstrated that the pain scores at rest and on movement at 48 hours were significantly lower than those in the control group. On the other hand, the meta-analysis performed by Duan et al 45 showed no significant difference in pain scores at rest and on movement at 48 hours between the ESPB and control group. In the present meta-analysis, although no significant differences were noted in pain scores at rest at 48 hours between the ESPB group and control group, the pooled effect was associated with significant heterogeneity.…”
Section: Discussionmentioning
confidence: 87%
“…Of note, the authors of the meta-analysis cautioned that the quality of pooled findings was judged to be low to moderate. In addition, none of the pooled studies had used continuous ESPB for postoperative analgesia 49,50…”
Section: Regional Anesthesiamentioning
confidence: 99%